The improving mathematical reasoning ability of Junior High School Students using the Constructivism Approach assisted by animation videos - Wildayani, Wildayani; Marhami, Marhami; Mursalin, Mursalin; Saputra, Eri; Wulandari, Wulandari (Universitas Malikussaleh, 2021)
The purpose of this study was to determine the increase in mathematical reasoning abilities of junior high school students using a constructivism approach assisted by animated videos on the comparison material of class VII MTsS Jabal Nur. The approach used in this research is a quantitative research approach with a quasi-experimental type of approach. The population in this study were all students of class VII consisting of 10 classes and the sample used was class VII-5 as the experimental class as many as 25 students and class VII-6 as the control class as many as 26 students. The experimental class students were taught using a constructivism approach assisted by animated videos, while the control class was taught using a scientific approach. The data was collected by giving a pretest-posttest and the data were analyzed using the t-test and obtained a result of 0.00. In accordance with the test criteria, the value in the sig column < 0.05 then is rejected. From the statistical significance of the t-test is 0.00 less than 0.05. Then is rejected, H_a is accepted. The results of the analysis of student responses to constructivism approach learning assisted by animated videos show that the overall average is in the very good category. This shows students that using a constructivism approach assisted by animated videos gets a positive response from students. The learning process using this approach can improve students ‘abilities in learning mathematics and can increase students’ desire to learn and student activity.